Syncytiotrophoblast-Derived Extracellular Vesicles in Pathophysiology of Preeclampsia - Han, Cha; Han, Lulu; Huang, Pengzhu; Chen, Yuanyuan; Wang, Yingmei; Xue, Fengxia (Frontiers in Physiology, 2019)
Preeclampsia is a common obstetric complication associated with pregnancy and it endangers lives of the mother and the infant. The histopathological changes associated with preeclampsia include systemic endothelial dysfunction, persistent inflammatory state, and coagulation and fibrinolysis dysregulations. Preeclampsia is considered to be caused by the systemic vasoconstriction of small arteries and disruption of the endothelial integrity, resulting in hypertension, proteinuria, and multiple organ dysfunction. However, mediators that trigger or propagate the pathology of preeclampsia remain poorly defined. Syncytiotrophoblast-derived extracellular vesicles (SDEVs) are increasingly recognized as a key mediator for the development of preeclampsia, but the underlying mechanisms through which these SDEVs are released and induce systemic responses are not fully understood. This review focuses on multiple roles of SDEVs in the pathogenesis of preeclampsia.